Evaluating #MeToo: The Perspective of Criminal Law Theory. Issue 5 (August 2021) - Hörnle, Tatjana
Abstract: The article describes the #MeToo-movement in the United States and Germany and discusses the merits and problems of this social phenomenon. It highlights the fact that some features of #MeToo (blaming and sanctioning wrongdoers) resemble those of criminal punishment and thus require careful justification. In the final part, the author examines the impact of the #MeToo-movement on criminal law reform.